The Role of Game Technologies in Teaching Grammar - Shodieva Gulnoza Nematilloevna, (European Journal of Life Safety and Stability (2660-9630), 2023)
The purpose of the study of this article is to develop a set of games aimed at the formation of grammar skills in young language learners in foreign language lessons and analyze scientific, psychological, pedagogical and methodological literature on the definition of grammatical skill and ways of its formation in the educational process.